PENGARUH AUDIT INTERNAL, SISTEM PENGENDALIAN MANAJEMEN, GAYA KEPEMIMPINAN, KAPABILITAS SUMBER DAYA MANUSIA, TOTAL QUALITY MANAGEMENTDALAM MEWUJUDKAN GOOD GOVERNANCE PADA BADAN PUSAT STATISTIK KABUPATEN JEMBER - Adelia, Arin Putri; Astuti, Diana Dwi; Rachmawati, Lia (RISTANSI: Riset Akuntansi, 2023)
This study aims to determine the effect of internal audit, management control system, leadership style, human resource capability, and total quality management in realizing good governance at the Central Bureau of Statistics of Jember Regency. The population of this study was employees of the Jember Regency Central Bureau of Statistics. The population of this research object is 42 people. The sampling technique used in this study was a Saturated Sample so a sample of 42 people was obtained. The data collection method used in this study was by distributing questionnaires. The data analysis method used is Multiple Linear Regression Analysis. The results of this study indicate that internal audit, management control systems, leadership styles, human resource capabilities, and total quality management simultaneously influence the realization of good governance at the Central Bureau of Statistics of Jember Regency. Partially, human resource capabilities are influential in realizing good governance. Meanwhile, internal audit, management control systems, leadership style, and total quality management have no partial effect on realizing good governance at the Central Bureau of Statistics of Jember Regency.